Superconductivity suppression and bilayer decoupling in Pr-substituted YBa 2 Cu 3 O 7− δ - Jinming Yang; Zheting Jin; Siqi Wang; Camilla M. Moir; Mingyu Xu; Brandon Gunn; Rourav Basak; Joshua R. Evans; Xian Du; Zhibo Kang; Keke Feng; Makoto Hashimoto; et al. (Proceedings of the National Academy of Sciences, 2026)
The mechanism behind superconductivity suppression induced by Pr substitutions in YBa 2 Cu 3 O 7− δ (YBCO) has been a mystery since its discovery: in spite of being isovalent to Y 3+ with a small magnetic moment, it is the only rare-earth element that has a dramatic impact on YBCO’s superconducting properties. Using angle-resolved photoemission spectroscopy (ARPES) and DFT+ U calculations, we uncover how Pr substitution modifies the low-energy electronic structure of YBCO. Contrary to the prevailing Fehrenbacher–Rice (FR) and Liechtenstein–Mazin (LM) models, the low-energy electronic structure contains no signature of any f -electron hybridization or additional f -state Fermi surface sheets. Yet, strong electron doping is observed primarily on the antibonding Fermi surface. Meanwhile, we reveal major electronic structure modifications to Cu-derived states with increasing Pr substitution: a pronounced CuO 2 bilayer decoupling and enhanced hopping along the CuO chain, implying indirect electron-release pathways beyond simple 4 f state ionization. Our results challenge the long-standing FR/LM mechanism, and establish Pr substituted YBCO as a potential platform for exploring correlation-driven phenomena in coupled 1D–2D systems.